The role of malachite nanorods for the electrochemical reduction of CO2 to C2 hydrocarbons. (20th February 2019) - Spodaryk, Mariana; Zhao, Kun; Zhang, Jie; Oveisi, Emad; Züttel, Andreas
Abstract: The electrochemical reduction of CO2 to higher hydrocarbons is a very challenging process that has high potential for the storage of large amounts of renewable energy with a high gravimetric and volumetric energy density. The distribution of hydrocarbons from the electrocatalytic reduction of CO2 is primarily determined by the interaction of the cathode material with the CO2 in the electrolyte. While the research on the electrochemical CO2 reduction focuses on the cathode metal and surface structure of the metals, recently evidence was found that the metal itself may not be the active species but rather the product formed from the metal and CO2 . In this paper, we report about the synthesis, catalytic activity and selectivity of nanostructured metal carbonate, i.e. malachite, as a highly active catalyst for the electrochemical synthesis of C2 hydrocarbons. These first results obtained on Cu2 (OH)2 CO3 nanorod-structured "trees" show that carbonate, not the pure metal, is the active catalytic species. This new catalyst favors the production of ethylene (C2 H4 ) and ethane (C2 H6 ) with significantly higher Faradaic efficiency than that of the pure Cu surface. Highlights: Malachite nanostructured "trees" catalyse the CO2 reduction to C2 H4 and C2 H6 . Carbonate, not the pure metal, is the active species for CO2 reduction process. Spontaneously formed malachite is more stable than chemically oxidized one.